Effect of target-enriched multiplex polymerase chain reaction on patient outcomes and costs during the 2013–14 influenza season. Issue 4 (August 2017) - Hassoun, A.; Huff, M.D.; Asis, E.; Chahal, K.; Azarbal, A.; Lu, S.
Summary: The US Centers for Disease Control and Prevention recommends the initial use of rapid antigen influenza diagnostic test (RIDT) for the detection of influenza A (H1N1-09). Nasopharyngeal samples were tested from 246 patients for H1N1-09 using target-enriched multiplex polymerase chain reaction (TEM-PCR), of which 163 were additionally tested via RIDT. RIDTs had a sensitivity of 18.7% compared with TEM-PCR as the reference standard. Patients with false-negative RIDTs were withheld from 111 days of oseltamivir and 65 days of isolation. Patients negative for H1N1 via TEM-PCR had antiviral therapy immediately stopped, thereby evading 408 days of oseltamivir and 315 days of unnecessary isolation. This cost avoidance saved US$208, 982.